1992
DOI: 10.1177/0143034392131001
|View full text |Cite
|
Sign up to set email alerts
|

Bullying: Perceptions of Adolescent Victims in the Midwestern USA

Abstract: Retrospective data were collected from adolescent students in order to clarify perceptions of victimization by bullies in small-town midwestern schools. Seventy-two percent of females and 81 percent of male respondents felt that they had experienced bullying at some point in their student careers (76.8 percent overall). Fewer students were considered chronic victims as self-reported severity of bullying increased. Though there are some difficulties in making a direct comparison, preliminary results indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
205
0
10

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(236 citation statements)
references
References 13 publications
16
205
0
10
Order By: Relevance
“…A recent call by peer victimization researchers suggests that those in the field should begin to focus on the variations in children's responses to peer victimization and what factors may serve to protect these children from its negative outcomes (see . In a recent study of middle and high school students evaluating their victimization experiences throughout school, findings indicated that although a significant number of students report being victimized at some point in school (nearly 76.8%), only about 14% estimated significant trauma affecting their social and academic outcomes (Hoover, Oliver, & Hazler, 1992). These findings shed light on the need to not only study children who report negative effects from victimization, but the need to study those who report little to no negative effects from victimization.…”
Section: Peer Victimization and Adjustment Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent call by peer victimization researchers suggests that those in the field should begin to focus on the variations in children's responses to peer victimization and what factors may serve to protect these children from its negative outcomes (see . In a recent study of middle and high school students evaluating their victimization experiences throughout school, findings indicated that although a significant number of students report being victimized at some point in school (nearly 76.8%), only about 14% estimated significant trauma affecting their social and academic outcomes (Hoover, Oliver, & Hazler, 1992). These findings shed light on the need to not only study children who report negative effects from victimization, but the need to study those who report little to no negative effects from victimization.…”
Section: Peer Victimization and Adjustment Outcomesmentioning
confidence: 99%
“…There are current researchers, though, who suggest that the landscape of peer victimization is much more heterogenous than past research has indicated (Hanish & Guerra, 2002;KochenderferLadd & Ladd, 2001;Kochenderfer-Ladd & Skinner, 2002;Goodman & Southam-Gerow, 2010). In the face of victimization from peers, some studies suggest there are children who report little to no effects on their adjustment (Hoover, Oliver, & Hazler, 1992 …”
Section: Defining Peer Victimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research indicates that schoolchildren tend to attribute causes of bullying to the victim by interpreting him or her as deviant or different (e.g., different appearance, behavior, clothes, or way of speaking) (Bosacki et al, 2006;Buchanan & Winzer, 2001;Frisén, Holmqvist, & Oscarsson, 2008;Hamarus & Kaikkonen, 2008;Hazler & Hoover, 1993;Hoover, Oliver, & Hazler, 1992;Teräsahjo & Salmivalli, 2003;Varjas et al, 2008). A recent study has shown that peer-perceived atypical behavior of a child is in fact related to higher levels of social rejection and peer victimization among schoolchildren (DeRoiser & Mercer, 2009).…”
Section: Children's Representations On Bullying Causesmentioning
confidence: 99%
“…O problema é que, muitas vezes, esses alunos não conheceram outras formas de se relacionar senão pela agressão, submissão e pelo menosprezo (Hoover, Oliver, & Hazler, 1992). Não seria, então, o caso de ajudá-los a confirmar que o outro a quem desprezam se sente tão mal quanto eles se sentiriam na mesma situação?…”
Section: Conclusõesunclassified